To the Problem of the Lexical and Grammatical Composition of Avar Paremiological Units, which Characterize Women (Proceedings of Southern Federal University. Philology, 2020)
The given article describes the features of the lexical and grammatical composition of Avar gender paremiological units characterizing women: substantive and verbal evaluative and symbolic lexical units that form positive and negative images of women are identified and interpreted; characterized by connotative components of gender-related paremiological images; the adversary-concessive semantic relations characteristic for the studied paremiological units were demonstrated; the attention is paid to the peculiarities of functioning of adjectival components in the described proverbs and sayings (participles, full and short forms of adjectives) in the predicative function; determined the role of the alogism principle, on the basis of which separate national-cultural images of women are built; characterized oppositionally (antonymously) opposed lexical units that form alogism relations; identified some unusual morphological forms with the value of a deprecated negation, used in the composition of expressive syntactic structures; the national-cultural components of some symbolic lexical components of the studied paroemiological units are determined.Key words: Avar language, paremias, female images, lexical and grammatical features, principle of alogism , connotations, semantic relations.DOI 10.18522/1995-0640-2020-1-53-61